State of the Art Technologies Used as a Rescue Response During Recovery from Structural Collapse - Norbert TUŚNIO (Nowoczesne technologie stosowane w działaniach ratowniczych podczas likwidacji skutkówkatastrofy budowlanej, 2017)
This paper is a description of the state of the art technical equipment procured during the execution of the project ‟Innovative solutions for stabilizing building and engineering structures as a rescue response during structural collapse recoveryˮ. The project is financed by the National Centre for Research with an execution frame of 2015 to 2017, and carried out by the consortium of the Main School of Fire Service in Warsaw, The Fire Service College of the State Fire Service in Kraków, the Scientific and Research Centre for Fire Protection – National Research Institute and CMGI Sp. z o.o. The technical specifications are presented for an unmanned air vehicle (UAV) built on commission for the Main School of Fire Service; the UAV can be used to monitor rescue mission operations at the sites of collapsed building
Keywords: Nowoczesne technologie w działaniach ratowniczych